Psychosocial determinants of treatment-seeking behavior among vesicovaginal fistula women in North-West Nigeria: A pilot study - Nasiru, Muhammad Anka; Ahmad, Abd Halim; Md Dahlan, Nuarrual Hilal (2016)
The purpose of this paper is to examine few sample data quantitatively on the psycho social determinants (lack of decision-making, negative attitude of health personnel, stigma, poor social support, poor transportation and poor quality of life) of treatment seeking behavior among women with Vesicovaginal Fistula (VVF) disease in two states of north-west Nigeria.This study used survey approach to gather 50 usable questionnaires, following simple random sampling method.The research model produces six factors, which were applied as psycho social determinants of treatment-seeking behavior.Thus, validity and reliability of the measurement instruments used in this study was examined by panel of experts, and the few data sample was analyzed through statistical package for social science (SPSS) software v22. Results of pilot study established that 7 out of the 8 adapted measurement instruments are valid and reliable, 1 of the instruments is valid but has reliability issue, which based on several literatures might be resolved when sample size and or number of items for the particular construct are increased in the main study.